Persuasive technology in the Islamic perspective: the principles and strategies - Bawazir, Mohammed Abdullah; Mahmud, Murni; Abdul Molok, Nurul Nuha (IIUM Press, International Islamic University Malaysia, 2019)
The employment of persuasive technology in education, computing, sales, health, and environment is dramatically increasing. Persuasive technology is powerful in changing the attitudes and behaviours of end users. This paper begins by presenting the ethics of persuasive technology which are relevant to Islamic values and beliefs, and how the concept of persuasion had been applied in Islam practices to influence people. It explores how persuasive technology and its design factors presented in FBM are related to the Islamic practices proven in the Quran and Hadith. Additionally, this paper discusses persuasive technology strategy tools and their activities from Islamic prospective. The paper also examines in depth how Islamic concepts improve the perception of persuasive technology as an interactive computing system which is able to modify attitudes and behaviours. Essentially, this paper also demonstrates how practices and principles of the design factors and strategy tools of persuasive technology have been identified and utilized in early Islamic age. Those principles and strategies are further analyzed from Quran verses and Hadith that are of particular relevance. The conceptual results claim that Islamic principles are a contemporary and universal religion that takes care of the persuasive technology aspects and view of the critically of persuasive technology to Muslim society.